A collagen hydroxyapatite scaffold allows for binding and co-delivery of recombinant bone morphogenetic proteins and bisphosphonates - O'BRIEN, FERGAL (My University, 2014)
An emerging paradigm in orthopedics is that a bone-healing outcome is the product of the anabolic (bone-forming) and catabolic (bone-resorbing) outcomes. Recently, surgical and tissue engineering strat- egies have emerged that combine recombinant human bone morphogenetic proteins (rhBMPs) and bis- phosphonates (BPs) in order to maximize anabolism and minimize catabolism. Collagen-based scaffolds that are the current surgical standard can bind rhBMPs, but not BPs. We hypothesized that a biomimetic collagen?hydroxyapatite (CHA) scaffold would bind both agents and produce superior in vivo outcomes. Consistent with this concept, in vitro elution studies utilizing rhBMP-2 ELISA assays and scintillation counting of 14C-radiolabeled zoledronic acid (ZA) confirmed delayed release of both agents from the CHA scaffold. Next, scaffolds were tested for their capacity to form ectopic bone after surgical implanta- tion into the rat hind limb. Using CHA, a significant 6-fold increase in bone volume was seen in rhBMP-2/ ZA groups compared to rhBMP-2 alone, confirming the ability of ZA to enhance rhBMP-2 bone formation. CHA scaffolds were found to be capable of generating mineralized tissue in the absence of rhBMP-2. This study has implications for future clinical treatments of critical bone defects. It demonstrates the relative advantages of co-delivering anabolic and anti-catabolic agents using a multicomponent scaffold system. Crown
PUBLISHED
Keywords: Zoledronic acid; Bisphosphonate